AUDIT OF HYDATIDIFORM MOLES IN A NON-SPECIALIST GYNAECOLOGY TERTIARY HOSPITAL – OUR HYDATIDIFORM MOLE INCIDENCE AND REFERRED CASE DIAGNOSES SHOW NO SIGNIFICANT DIFFERENCE TO THAT OF MAJOR INTERNATIONAL STUDIES. (February 2015) - Holmes, Melissa; Pyman, Jan; McLean, Catriona
Abstract : Aim: Alfred Health is a non-specialist gynaecology tertiary hospital. We retrospectively analysed the ratio of hydatidiform moles to products of conception (POC) and statistically compared data with large prospective international studies to quality assure our current referral practice. Method: All POC and hydatidiform moles over 5 years (1/1/2009–31/12/2013) were database searched. POCs suspicious for hydatidiform mole, without classic morphology, were referred to Royal Women's Hospital, Melbourne, for review and ancillary techniques. Numbers of hydatidiform moles and specialist referrals were compared with international data, and Fisher's exact test used to determine statistical significance. Results: Total 789 POC: 22 (3%) hydatidiform moles; 16 (2%) partial moles (12 referred, 4 not-referred), 6 (0.7%) complete moles (4 referred, 2 not-referred). Total referred 28 (4%): 16 (57%) hydatidiform moles; 12 partial moles (10 requiring ploidy, 1 p57, 1 morphology); 4 complete moles (3 requiring p57, 1 morphology); 12 (43%) non-molar (11 ploidy, 1 p57). Discussion: Compared to international studies, our hydatidiform mole incidence1 and referred case diagnoses2 do not significantly differ ( p = n.s.), confirming our referral pattern is on par with these studies and needs no significant change. Implementation of p57 immunohistochemistry may reduce our referred complete moles although specialist opinion will continue to be sought.